2010
DOI: 10.1007/s11033-010-0443-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in methylenetetrahydrofolate reductase and in cysthationine beta synthase: is there a link to homocysteine levels in peripheral arterial disease?

Abstract: Peripheral arterial disease (PAD) is an atherosclerotic disturbance characterized by a progressive obstruction of lower limb arteries. Many risk factors associated with PAD development have being reported in the literature. The present study aimed to investigate whether mutations in the methylenetetrahydrofolate reductase (MTHFR) or in the cystathionine beta synthase (CBS) genes are associated with higher levels of homocysteine and the risk of PAD in patients from Brazil. This study analyzed 39 patients with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The MTHFR gene polymorphism was reported to be associated with hyperhomocysteinaemia which has deleterious effects on the cardiovascular system [13,28]. Hence, psoriasis vulgaris patients with MTHFR gene polymorphism may be at greater risk of cardiovascular diseases and thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MTHFR gene polymorphism was reported to be associated with hyperhomocysteinaemia which has deleterious effects on the cardiovascular system [13,28]. Hence, psoriasis vulgaris patients with MTHFR gene polymorphism may be at greater risk of cardiovascular diseases and thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic remethylations of homocysteine to methionine by 5-methyltetrahydrofolate homocysteine methyltransferase rely heavily on the adequate levels of vitamin B 12 and folic acid. Therefore, the deficiencies of the Vitamin B 12 and folic acid will lead to hyperhomocysteinaemia and hypomethioninaemia [13-16]. …”
Section: Introductionmentioning
confidence: 99%
“…28,30,37,40,41,4348 Six studies showed no significant difference in mutation prevalence between patients with PAD and healthy controls. 37,40,42,43,45,46 However, two studies showed a higher prevalence of the MTHFR 667T allele or TT genotype in patients with PAD than in individuals without cardiovascular disease. 41,44 The results of two meta-analysis were also conflicting.…”
Section: Nutritional Factors and Risk Of Padmentioning
confidence: 99%
“…One of the major determinants of Hcy levels is the folic acid (folate). Accordingly, folate deficiency as well as MTHFR gene polymorphism can affect plasma Hcy levels causing hyperhomocysteinemia . Frosst et al demonstrated the association of the homozygous mutant genotype (677TT) with mild hyperhomocysteinemia.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, folate deficiency as well as MTHFR gene polymorphism can affect plasma Hcy levels causing hyperhomocysteinemia. 7 Frosst et al 8 demonstrated the association of the homozygous mutant genotype (677TT) with mild hyperhomocysteinemia. Then, it became evident that this relationship was found only in individuals with folate deficiency.…”
mentioning
confidence: 99%